The Timeliness Initiative: Continuous Process Improvement for Prompt Initiation of Radiation Therapy Treatment - Nzhde Agazaryan, PhD (Advances in Radiation Oncology, 2020)
Purpose: The ambulatory patient experience is heavily influenced by wait times for provider care. Delayed patient visit start times may negatively affect overall satisfaction, and increased wait times affect the perception of the information, instructions, and treatment given by health care providers. Improving institutional practices overall requires the determination of the essential quality metrics that will make such an achievement possible. A protracted time leading up to the initiation of radiation therapy may promote poor satisfaction and perceived quality of care for both patients and referring providers alike, which may then create a barrier to patients being treated with radiation therapy. This institution piloted and sucessfully completed a study into improving the timeliness of initiation of patient radiation therapy for our patients. Methods and Materials: This work sought to identify inefficiencies in radiation therapy treatment planning to shorten the time each patient waited for treatment. We examined the time between simulation to the start of the first fraction of treatment. This period includes simulation, contouring, treatment planning, and quality assurance of the plan. Results: Before the study, the planning process would typically take 2 weeks. Target and organs-at-risk contouring were found to be the main inefficiency delaying treatment start dates. This delineating process includes drawing contours on radiologic images, typically computed tomography and magnetic resonance imaging. We focused on the time needed for the contouring process to be completed and took steps to increase efficiency. The length of time from simulation to contour approval was decreased by more than 60%, a reduction from an average of more than 4 days to less than 1.5 days. Overall planning time dropped from 2 weeks to less than 5 days. Conclusions: Process improvements and implementation of task-specific tools improved the timeliness of patient treatments, reducing the overall planning time from simulation to treatments to less than 5 days. Continuous monitoring and modification of these processes revealed that the successes achieved toward better quality of care have been sustained.